The Ontology of Sponsality in Karol Wojtyła’s Thought - Domiciano Formenton, Giovani; Fernandes, Marcio; Solano Durán, José Rafael (Verbum Vitae, 2024)
This article presents a teleological perspective on spousal love, exploring Wojtyła’s thoughts on sponsality as the divine plan for human love. The investigation is important because spousal love is presented in the Bible and in Christian mysticism as an analogy for God’s love and for the eschatological mystery. It is also necessary considering the social impact of family experiences on issues such as mental health, parenthood, criminality, and antisocial behavior. This bibliographical research is based on Wojtyła’s Love and Responsibility and The Catecheses on Human Love in the Divine Plan. It is divided into four sections: the human person as a relational being, biblical texts about spousal love, Wojtyła’s teaching on this category, and the teleological aspects observed in this teaching. Our findings indicate that for Wojtyła, spousal love is the teleological reality of the human person, supported by three main aspects. (1) According to Wojtyła’s personalistic thought, God must be understandable when inviting a person to a definitive relationship. The Bible uses spousal relationship to indicate God’s definitive alliance. (2) Wojtyła understands spousal love as the original sacrament of trinitarian relation. He states that the human person is the image and likeness of God because it was created as man and woman. (3) Spousal love is a total gift of self that leads the person to blessedness and fulfillment. It is the only way to imitate Christ in his kenosis.